The Digital Uncanny: Re-imagining Folklore and the Supernatural in Nigerian Hypertext and Interactive Fiction - Augustine A. A Edung; Lydia Justin Adamu; Patrick Ogar; Arit Ansa Archibong (Universitas Negeri Makassar, 2025)
This paper argues that interactive digital formats, including hypertext archives, social media storytelling, and narrative video games, constitute a uniquely potent medium for the contemporary re-imagination of Nigerian folklore and the supernatural. We propose the concept of the “Digital Uncanny” to describe the aesthetic and epistemological effect generated when familiar folkloric content is estranged and renewed through its remediation into nonlinear, participatory, and rule-based digital code. This uncanniness arises from a resonant formal alignment: the structural affordances of digital interactivity mirror the ontological principles of indigenous cosmologies, which often privilege multiplicity, cyclicality, and agential encounter over linear causality. Through close analysis of three distinct case studies—the archival hypertext of the Digital Okike project, the participatory viral threads of the #FolkloreThursday phenomenon on social media, and the systemic ritual gameplay of the Yoruba-inspired video game Ọlọjọ, this study demonstrates that digital literature does not merely document tradition but actively performs it. These works transform passive readers into active participants within digitally mediated ritual spaces, thereby reasserting the relevance and adaptability of indigenous knowledge systems in a global digital age. Ultimately, this research positions Nigerian digital storytelling as a vital site of cultural innovation, where the future of folklore is shaped through interactive, uncanny, and deeply contemporary forms.